Pembuatan dan Pemanfaatan Kain Shibori sebagai Produk Lanjutan - Nernere, Maria Setyaningsih (Jurnal Atma Inovasia, 2021)
Kelurahan Giripurwo is a cultural village that has abundant cultural wealth. There is a potential culture brought by the government to add to the cultural richness of the Giripurwo Village called shibori cloth. The use of shibori cloth can be one of the cultural potentials that can be maximized by Giripurwo villagers to add cultural and economic value to this village. To explore the function of shibori cloth as a cultural and economic potential that can positively contribute to the Giripurwo Village, online observations are made by conducting literature studies through websites, books, journals, articles, and other sources relevant to the development of the potential of shibori cloth as a cultural asset. The techniques of making shibori can be categorized into 6 different techniques, namely, Kanoko, Miura, Arashi, Itajime, Kumo, and Nui. Different techniques will produce different variations. This variation can be a positive thing because, in its later economic function, consumers are not limited by a limited choice of products. The use of the online marketplace also plays an important role in maximizing the economic function that can be achieved from the shibori cloth products produced by the people of Giripurwo Village.